Preparation method of Cu-Ta composite wire

Through powder discharge plasma sintering, rotary forging and drawing processes, combined with heat treatment, the dense structure and duplex interface of Cu-Ta composite wire are optimized, which solves the problems of complex production process and difficult to improve performance, and realizes the high strength, high conductivity and uniform structure of Cu-Ta composite wire, which is suitable for mass production.

CN119501074AActive Publication Date: 2025-02-25NORTHWEST INSTITUTE FOR NONFERROUS METAL RESEARCH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411688260.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-25
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing Cu-Nb composite wire preparation process is complex and the performance is difficult to break through, and the preparation process of Cu-Ta composite material also has the problem of complex processes and is not suitable for mass production.

Method used

The powder discharge plasma sintering + rotary forging + drawing process is adopted, combined with heat treatment, to optimize the dense structure and duplex interface of Cu-Ta composite wire to improve its performance.

Benefits of technology

The high strength, high conductivity and uniform structure of Cu-Ta composite wire is achieved, which solves the problems of complex production process and difficult to improve the performance of Cu-Nb composite wire, and reduces the production difficulty and cost, which is suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119501074A_ABST
    Figure CN119501074A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a Cu-Ta composite wire. The method comprises the following steps: 1, ball-milling and mixing Cu powder and Ta powder; 2, spark plasma sintering; 3, hot extrusion treatment; 4, primary rotary swaging treatment; 5, heat treatment; 6, secondary rotary swaging treatment; and seventhly, straightening and acid pickling are conducted after drawing treatment, and the Cu-Ta composite wire is obtained. According to the method, the powder spark plasma sintering, rotary swaging and drawing processes are combined with heat treatment, good matching of a compact structure and a two-phase interface of the Cu powder and the Ta powder is achieved, the performance of the Cu-Ta composite wire is improved, the high-strength and high-conductivity Cu-Ta composite wire with a uniform structure is obtained, and the method is simple in process, high in operability, low in cost and suitable for industrial production. The method is suitable for early-stage preparation of composite long wires, and the product is suitable for the field of pulse magnets.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal alloy material processing, and in particular relates to a method for preparing a Cu-Ta composite wire. Background Art

[0002] High-strength and high-conductivity copper-based composite materials are metal materials with excellent electrical transport properties, mechanical properties and thermal stability. They are currently widely used in many fields such as high pulse magnetic field conductor materials, switching switches, electrical contactors, lead frames and electronic devices. Among them, Cu-Nb, Cu-Ag, and Cu-Cr composite materials have achieved important breakthroughs in the application end.

[0003] The most widely used form of this type of material is wire. At present, the conductor material used in pulse magnets is mainly Cu-Nb composite wire. The role of the Cu substrate is to ensure the good electrical conductivity of the material, and the excellent mechanical properties mainly come from the contribution of the Nb core wire in the substrate. Since there is basically no solid solubility between copper and niobium, and it is difficult to form an intermediate phase compound, the preparation method of this material is mainly large plastic deformation. However, due to the inherent characteristics of the Cu-Nb composite material itself and the coordinated deformation ability between copper and niobium, the Cu-Nb wire obtained by bundle drawing and multiple composites has reached its processing limit. On the basis of ensuring good electrical conductivity, the material strength can no longer be further improved through preparation process and component design. Taking the Cu-Nb wire obtained by winding + bundle drawing and powder sleeve + bundle drawing as an example, the strength of a single-core non-bundled composite wire is generally between 250MPa and 400MPa. In particular, although the winding + bundle drawing method has a slight advantage in performance, its preparation process is relatively cumbersome and the process is complicated, which greatly increases the cost of the finished wire.

[0004] Compared with Nb alloy, Ta alloy has more obvious advantages as a reinforcing core wire. Metal tantalum and its alloys have high density, high melting point, extreme corrosion resistance, small thermal expansion coefficient, excellent high temperature strength, and great ductility. They are increasingly valued and used to make electronic devices, capacitors, etc. Due to the excellent properties of metal tantalum, people hope to expand and broaden its application field by preparing Cu-Ta alloy materials with better performance. Because with the continuous development of high pulse magnetic fields, the performance requirements for the required conductor materials will be higher, so it is of practical significance to prepare Cu-Ta composite materials with better performance. With the further development of high pulse magnetic fields, it will become an inevitable trend for Cu-Ta composite materials to gradually replace Cu-Nb microcomposites for application in high pulse magnetic fields. In the past, Cu-Ta composite materials often involved high-energy ball milling, cumulative rolling, etc., and the process technology was relatively complicated. There were many obstacles in long-line preparation, which was not suitable for mass production in related industries. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a method for preparing a Cu-Ta composite wire in view of the deficiencies of the above-mentioned prior art. The method realizes a good dense structure between copper and tantalum through powder discharge plasma sintering + rotary forging + drawing process combined with heat treatment, so that the two-phase interface is significantly optimized, the performance of the Cu-Ta composite wire is improved, and a high-strength and high-conductivity Cu-Ta composite wire with a uniform structure is obtained, which solves the problem that the preparation process of Cu-Nb composite wire in the prior art is complicated and the performance is difficult to break through.

[0006] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a Cu-Ta composite wire, characterized in that the method comprises the following steps:

[0007] Step 1: Using a planetary ball mill to mix Cu powder and Ta powder to obtain Cu-Ta mixed powder;

[0008] Step 2: Spark plasma sintering the Cu-Ta mixed powder obtained in step 1 to obtain a Cu-Ta columnar alloy;

[0009] Step 3: hot extruding the Cu-Ta columnar alloy obtained in step 2 to obtain a Cu-Ta extruded rod;

[0010] Step 4: performing a rotary forging process on the Cu-Ta extruded rod obtained in step 3 to obtain a Cu-Ta single rotary forging wire;

[0011] Step 5, heat treating the Cu-Ta single rotary forging wire obtained in step 4;

[0012] Step 6, subjecting the Cu-Ta primary rotary forging wire heat-treated in step 5 to secondary rotary forging to obtain a Cu-Ta secondary rotary forging wire;

[0013] Step 7: The Cu-Ta secondary rotary forging wire obtained in step 6 is subjected to drawing treatment to obtain a Cu-Ta drawn wire, and the Cu-Ta composite wire is obtained after straightening and pickling.

[0014] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that the particle sizes of the Cu powder and the Ta powder in step 1 are 5μm to 15μm and 65μm to 50μm, respectively. Based on the difference in deformation ability between Cu and Ta, the present invention controls the particle sizes of the Cu powder and the Ta powder, which is beneficial to improving the deformation ability of the wire.

[0015] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that the mass purity of the Cu powder and Ta powder in step 1 is above 99.95%.

[0016] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that the ball milling mixed powder treatment in step 1 adopts a rotation speed of 350rpm, a time of 40h, a ball-to-material mass ratio of 15:1, and the grinding balls include 8mm diameter grinding balls, 5mm diameter grinding balls, and 2mm diameter grinding balls in a quantity ratio of 3:5:2, and the ball milling atmosphere is an argon atmosphere. Usually, the powder loading operation before the ball milling mixed powder treatment is carried out under argon protection conditions, and the ball milling tank is always filled with argon atmosphere during the ball milling process to prevent oxidation of the Cu-Ta mixed powder.

[0017] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that the mass fraction of the Ta element in the Cu-Ta mixed powder in step 1 is 10% to 25%. The present invention controls the Ta element content to ensure the mechanical properties of the Cu-Ta composite wire while avoiding the influence of excessive Ta content on the conductive properties of the Cu-Ta composite wire.

[0018] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that the spark plasma sintering process in step 2 is: first heating to 600°C at a heating rate of 100°C / min, then heating to 950°C at a heating rate of 50°C / min, and controlling the pressure to 50MPa for 10 minutes.

[0019] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that the density of the Cu-Ta columnar alloy in step 2 is 97% to 99%. The present invention controls the density of the Cu-Ta columnar alloy, which is conducive to promoting the interface bonding between particles and eliminating defects such as holes, thereby improving the mechanical properties and conductive properties of the Cu-Ta composite wire.

[0020] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that, before the hot extrusion treatment in step 3, the Cu-Ta columnar alloy is heat treated at 900°C and kept warm for 30 minutes, and the mold for the hot extrusion treatment is preheated to 400°C, and the extrusion speed of the hot extrusion treatment is 5mm / s. By heat treating the Cu-Ta columnar alloy before the hot extrusion treatment and preheating the mold, combined with controlling the extrusion speed, rapid cooling during the hot extrusion process is avoided, and the heat treatment process is ensured to proceed smoothly.

[0021] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that the temperature of the heat treatment in step 5 is 700°C and the holding time is 3 hours. The heat treatment is performed after the first rotary forging process to eliminate the work hardening caused by the rotary forging process and avoid the core breaking phenomenon caused by work hardening during the subsequent deformation process; usually, the heat treatment is performed in an argon atmosphere throughout the process;

[0022] The above-mentioned method for preparing a Cu-Ta composite wire is characterized in that the diameter of the Cu-Ta columnar alloy in step 2 is 30 mm and the height is 25 mm to 27 mm; the diameter of the Cu-Ta extruded rod in step 3 is 7 mm; the diameter of the Cu-Ta extruded rod in the first rotary forging process in step 4 changes as follows: φ7.0 mm → φ6.6 mm → φ6.2 mm → φ5.9 mm → φ5.6 mm, and the corresponding processing amounts are 11.1%, 11.8%, 9.4%, and 9.9%, respectively; the Cu-Ta rotary forging in the second rotary forging process in step 6 The diameter of the wire changes as follows: φ5.6mm→φ5.3mm→φ5.0mm→φ4.7mm→φ4.4mm, and the corresponding processing amounts are 9.9%, 10.4%, 11.0%, 11.6%, and 12.3%, respectively; the diameter of the Cu-Ta secondary swaging wire changes during the drawing process described in step seven as follows: φ4.4mm→φ4.22mm→φ4.05mm→φ3.88mm→φ3.72mm→φ3.58mm→φ3.44mm, and the corresponding processing amounts are 11.5%, 9.40%, 9.39%, 8.35%, and 8.18%, respectively.

[0023] Compared with the prior art, the present invention has the following advantages:

[0024] 1. The present invention uses powder discharge plasma sintering + rotary forging + drawing process combined with heat treatment to form a good dense structure between Cu powder and Ta powder, and the two-phase interface forms a good match, thereby improving the performance of the Cu-Ta composite wire and obtaining a high-strength and high-conductivity Cu-Ta composite wire with a uniform structure.

[0025] 2. The Cu-Ta composite wire prepared by the present invention realizes a high-strength Ta fiber structure with good dispersion effect, and the average size of the core wire is about tens or hundreds of nanometers. Combined with heat treatment, a good interface bonding effect is formed between the Cu and Ta particles, and the interface bonding plays an enhancing role in strengthening mechanical properties.

[0026] 3. In the Cu-Ta composite wire prepared by the present invention, since Ta is extremely ductile, Cu-Ta is easier to refine than Cu-Nb, which reduces the difficulty of preparing the composite wire; at the same time, since the hardening effect of Ta is extremely obvious, the strengthening effect after processing is significantly higher than that of Nb. Therefore, compared with the Nb fiber of the Cu-Nb structure, the high-strength nano Ta fiber formed in the Cu-Ta composite wire of the present invention significantly improves the strength of the Cu-Ta composite wire.

[0027] 4. The Cu-Ta composite wire prepared by the present invention has excellent properties of Ta including high shear and elastic modulus, excellent ductility, corrosion resistance, etc., so that the Cu-Ta composite wire exhibits extremely high corrosion resistance, small thermal expansion coefficient, and high strength. At the same time, it has excellent tensile properties and conductive properties at a relatively large cross-sectional size. The process is simple, the operability is strong, and the cost is low. It is suitable for batch preparation of wires, and provides high-performance single-core basic wires for further wire composites.

[0028] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 The compressive stress-strain curves of the Cu-Ta composite wires prepared in Examples 1 to 4 of the present invention are shown.

[0030] Figure 2 Schematic diagram of the change in conductivity with the change in diameter φ during the deformation process of the Cu-Ta composite wire prepared in Examples 1 to 4 of the present invention. DETAILED DESCRIPTION

[0031] Example 1

[0032] This embodiment includes the following steps:

[0033] Step 1, using a planetary ball mill to perform ball milling and mixing of 144g of Cu powder with a particle size of 5μm to 15μm and a mass purity of more than 99.95% and 16g of Ta powder with a particle size of 65μm to 50μm and a mass purity of more than 99.95%, to obtain 160g of Cu-10%Ta mixed powder with a mass fraction of Ta element of 10%; the ball milling and mixing treatment adopts a rotation speed of 350rpm, a time of 40h, a ball-to-material mass ratio of 15:1, and the grinding balls include 8mm diameter grinding balls, 5mm diameter grinding balls, and 2mm diameter grinding balls with a quantity ratio of 3:5:2, and the ball milling atmosphere is an argon atmosphere;

[0034] Step 2: The Cu-10% Ta mixed powder obtained in step 1 is subjected to spark plasma sintering to obtain a Cu-10% Ta columnar alloy with a diameter of 30 mm and a height of 26 mm; the spark plasma sintering process is: firstly heated to 600°C at a heating rate of 100°C / min, then heated to 950°C at a heating rate of 50°C / min, and the pressure is controlled to 50 MPa for 10 minutes;

[0035] The density of Cu-10%Ta columnar alloy was measured by Archimedes drainage method and was over 97%;

[0036] Step 3, hot extruding the Cu-10% Ta columnar alloy obtained in step 2 to obtain a Cu-10% Ta extruded rod with a diameter of 7 mm and a length of 48 cm; before the hot extrusion treatment, the Cu-15% Ta columnar alloy is heat treated at 900° C. and kept warm for 30 minutes, and the die for the hot extrusion treatment is preheated to 400° C. The extrusion speed of the hot extrusion treatment is 5 mm / s, and the extrusion ratio is about 18;

[0037] Step 4, the Cu-10%Ta extruded rod obtained in step 3 is subjected to 4 passes of primary rotary forging treatment to obtain a Cu-Ta primary rotary forging wire; the diameter of the Cu-10%Ta extruded rod during the 4 passes of primary rotary forging treatment changes as follows: φ7.0mm→φ6.6mm→φ6.2mm→φ5.9mm→φ5.6mm, and the corresponding processing amounts are 11.1%, 11.8%, 9.4%, and 9.9%, respectively;

[0038] Step 5, heat treating the Cu-10%Ta single-spin forging wire obtained in step 4 at a temperature of 700° C. and a holding time of 3 h under argon atmosphere protection;

[0039] Step 6, subjecting the Cu-10%Ta primary rotary forging wire heat-treated in step 5 to 6 passes of secondary rotary forging treatment to obtain a Cu-10%Ta secondary rotary forging wire; during the 4 passes of secondary rotary forging treatment, the diameter of the primary Cu-10%Ta rotary forging wire changes as follows: φ5.6mm→φ5.3mm→φ5.0mm→φ4.7mm→φ4.4mm, and the corresponding processing amounts are 9.9%, 10.4%, 11.0%, 11.6%, and 12.3%, respectively;

[0040] Step seven, the Cu-10% Ta secondary swaging wire obtained in step six is ​​subjected to 6 drawing processes to obtain a Cu-10% Ta drawn wire, and after straightening and pickling, a Cu-10% Ta composite wire is obtained; during the 6 drawing processes, the diameter of the Cu-10% Ta secondary swaging wire changes as follows: φ4.4mm→φ4.22mm→φ4.05mm→φ3.88mm→φ3.72mm→φ3.58mm→φ3.44mm, and the corresponding processing amounts are 11.5%, 9.40%, 9.39%, 8.35%, and 8.18%, respectively.

[0041] After testing, the yield strength of the Cu-10% Ta composite wire prepared in this embodiment under tensile behavior is 368MPa, the tensile strength is 379MPa, the yield strength under compression behavior is 365MPa, and the conductivity is 79.3%IACS. Figure 1 and Figure 2As shown; after calculation, the total processing rate of the Cu-10% Ta composite wire prepared in this embodiment is 98.3%.

[0042] Example 2

[0043] This embodiment includes the following steps:

[0044] Step 1: Use a planetary ball mill to perform ball milling and mixing of 136 g of Cu powder with a particle size of 5 μm to 15 μm and a mass purity of more than 99.95% and 24 g of Ta powder with a particle size of 65 μm to 50 μm and a mass purity of more than 99.95% to obtain 160 g of Cu-15%Ta mixed powder with a mass fraction of Ta element of 15%; the ball milling and mixing treatment adopts a rotation speed of 350 rpm, a time of 40 h, a ball-to-material mass ratio of 15:1, and the grinding balls include 8 mm diameter grinding balls, 5 mm diameter grinding balls, and 2 mm diameter grinding balls in a quantity ratio of 3:5:2, and the ball milling atmosphere is an argon atmosphere;

[0045] Step 2: Spark plasma sintering the Cu-10% Ta mixed powder obtained in step 1 to obtain a Cu-15% Ta columnar alloy with a diameter of 30 mm and a height of 25 mm; the spark plasma sintering process is: first heating to 600°C at a heating rate of 100°C / min, then heating to 950°C at a heating rate of 50°C / min, and controlling the pressure to 50 MPa for 10 minutes;

[0046] The density of Cu-15%Ta columnar alloy was measured by Archimedes drainage method and was above 98%;

[0047] Step 3, hot extruding the Cu-15% Ta columnar alloy obtained in step 2 to obtain a Cu-15% Ta extruded rod with a diameter of 7 mm and a length of 46 cm; before the hot extrusion treatment, the Cu-15% Ta columnar alloy is heat treated at 900° C. and kept warm for 30 minutes, and the die for the hot extrusion treatment is preheated to 400° C. The extrusion speed of the hot extrusion treatment is 5 mm / s, and the extrusion ratio is about 18;

[0048] Step 4: The Cu-15%Ta extruded rod obtained in step 3 is subjected to 4 passes of single rotary forging treatment to obtain a Cu-15%Ta single rotary forging wire; the diameter of the Cu-10%Ta extruded rod during the 4 passes of single rotary forging treatment changes as follows: φ7.0mm→φ6.6mm→φ6.2mm→φ5.9mm→φ5.6mm, and the corresponding processing amounts are 11.1%, 11.8%, 9.4%, and 9.9%, respectively;

[0049] Step 5: heat-treating the Cu-15%Ta single-spin forging wire obtained in step 4 at a temperature of 700° C. and a holding time of 3 h under argon atmosphere protection;

[0050] Step 6, subjecting the Cu-15%Ta primary rotary forging wire heat-treated in step 5 to 6 passes of secondary rotary forging treatment to obtain a Cu-15%Ta secondary rotary forging wire; during the 4 passes of secondary rotary forging treatment, the diameter of the primary Cu-15%Ta rotary forging wire changes as follows: φ5.6mm→φ5.3mm→φ5.0mm→φ4.7mm→φ4.4mm, and the corresponding processing amounts are 9.9%, 10.4%, 11.0%, 11.6%, and 12.3%, respectively;

[0051] Step seven, the Cu-15%Ta secondary rotary forging wire obtained in step six is ​​subjected to 6 drawing processes to obtain a Cu-15%Ta drawn wire, and after straightening and pickling, a Cu-15%Ta composite wire is obtained; during the 6 drawing processes, the diameter of the Cu-15%Ta secondary rotary forging wire changes as follows: φ4.4mm→φ4.22mm→φ4.05mm→φ3.88mm→φ3.72mm→φ3.58mm→φ3.44mm, and the corresponding processing amounts are 11.5%, 9.40%, 9.39%, 8.35%, and 8.18%, respectively.

[0052] After testing, the yield strength of the Cu-15% Ta composite wire prepared in this embodiment under tensile behavior is 393MPa, the tensile strength is 411MPa, the yield strength under compression behavior is 392MPa, and the conductivity is 74.3%IACS. Figure 1 and Figure 2 As shown; after calculation, the total processing rate of the Cu-10%Ta composite wire prepared in this embodiment is 98.5%.

[0053] Example 3

[0054] This embodiment includes the following steps:

[0055] Step 1: Use a planetary ball mill to perform ball milling and mixing of 128 g of Cu powder with a particle size of 5 μm to 15 μm and a mass purity of more than 99.95% and 32 g of Ta powder with a particle size of 65 μm to 50 μm and a mass purity of more than 99.95% to obtain 160 g of Cu-20%Ta mixed powder with a mass fraction of Ta element of 20%; the ball milling and mixing treatment adopts a rotation speed of 350 rpm, a time of 40 hours, a ball-to-material mass ratio of 15:1, and the grinding balls include 8 mm diameter grinding balls, 5 mm diameter grinding balls, and 2 mm diameter grinding balls with a quantity ratio of 3:5:2, and the ball milling atmosphere is an argon atmosphere;

[0056] Step 2: Spark plasma sintering the Cu-20% Ta mixed powder obtained in step 1 to obtain a Cu-20% TaTa columnar alloy with a diameter of 30 mm and a height of 24 mm; the spark plasma sintering process is: first heating to 600°C at a heating rate of 100°C / min, then heating to 950°C at a heating rate of 50°C / min, and controlling the pressure to 50 MPa for 10 minutes;

[0057] The density of Cu-20%Ta columnar alloy was measured by Archimedes drainage method and was over 99%;

[0058] Step 3, hot extruding the Cu-20% Ta columnar alloy obtained in step 2 to obtain a Cu-20% Ta extruded rod with a diameter of 7 mm and a length of 44 cm; before the hot extrusion treatment, the Cu-20% Ta columnar alloy is heat treated at 900° C. and kept warm for 30 minutes, and the die for the hot extrusion treatment is preheated to 400° C. The extrusion speed of the hot extrusion treatment is 5 mm / s, and the extrusion ratio is about 18;

[0059] Step 4, the Cu-20%Ta extruded rod obtained in step 3 is subjected to 4 passes of primary rotary forging treatment to obtain a Cu-20%Ta primary rotary forging wire; the diameter of the Cu-20%Ta extruded rod during the 4 passes of primary rotary forging treatment changes as follows: φ7.0mm→φ6.6mm→φ6.2mm→φ5.9mm→φ5.6mm, and the corresponding processing amounts are 11.1%, 11.8%, 9.4%, and 9.9%, respectively;

[0060] Step 5: heat-treating the Cu-20%Ta single-spin forging wire obtained in step 4 at a temperature of 700° C. and a holding time of 3 h under argon atmosphere protection;

[0061] Step 6, subjecting the Cu-20%Ta primary rotary forging wire heat-treated in step 5 to 6 passes of secondary rotary forging treatment to obtain a Cu-20%Ta secondary rotary forging wire; during the 4 passes of secondary rotary forging treatment, the diameter of the primary Cu-20%Ta rotary forging wire changes as follows: φ5.6mm→φ5.3mm→φ5.0mm→φ4.7mm→φ4.4mm, and the corresponding processing amounts are 9.9%, 10.4%, 11.0%, 11.6%, and 12.3%, respectively;

[0062] Step seven, the Cu-20% Ta secondary swaging wire obtained in step six is ​​subjected to 6 drawing processes to obtain a Cu-20% Ta drawn wire, and after straightening and pickling, a Cu-20% Ta composite wire is obtained; during the 6 drawing processes, the diameter of the Cu-20% Ta secondary swaging wire changes as follows: φ4.4mm→φ4.22mm→φ4.05mm→φ3.88mm→φ3.72mm→φ3.58mm→φ3.44mm, and the corresponding processing amounts are 11.5%, 9.40%, 9.39%, 8.35%, and 8.18%, respectively.

[0063] After testing, the yield strength of the Cu-20% Ta composite wire prepared in this embodiment under tensile behavior is 430MPa, the tensile strength is 452MPa, the yield strength under compression behavior is 451MPa, and the conductivity is 69.9%IACS. Figure 1 and Figure 2 As shown; after calculation, the total processing rate of the Cu-20%Ta composite wire prepared in this embodiment is 97.7%.

[0064] Example 4

[0065] This embodiment includes the following steps:

[0066] Step 1: Use a planetary ball mill to perform ball milling and mixing of 120 g of Cu powder with a particle size of 5 μm to 15 μm and a mass purity of more than 99.95% and 40 g of Ta powder with a particle size of 65 μm to 50 μm and a mass purity of more than 99.95% to obtain 160 g of Cu-25%Ta mixed powder with a mass fraction of Ta element of 25%; the ball milling and mixing treatment adopts a rotation speed of 350 rpm, a time of 40 h, a ball-to-material mass ratio of 15:1, and the grinding balls include 8 mm diameter grinding balls, 5 mm diameter grinding balls, and 2 mm diameter grinding balls in a quantity ratio of 3:5:2, and the ball milling atmosphere is an argon atmosphere;

[0067] Step 2: The Cu-25% Ta mixed powder obtained in step 1 is subjected to spark plasma sintering to obtain a Cu-25% Ta columnar alloy with a diameter of 30 mm and a height of 24 mm; the spark plasma sintering process is: firstly heated to 600°C at a heating rate of 100°C / min, then heated to 950°C at a heating rate of 50°C / min, and the pressure is controlled to 50 MPa for 10 minutes;

[0068] The density of Cu-25%Ta columnar alloy was measured by Archimedes drainage method and was above 98%;

[0069] Step 3, hot extruding the Cu-25% Ta columnar alloy obtained in step 2 to obtain a Cu-25% Ta extruded rod with a diameter of 7 mm and a length of 44 cm; before the hot extrusion treatment, the Cu-25% Ta columnar alloy is heat treated at 900° C. and kept warm for 30 minutes, and the mold for the hot extrusion treatment is preheated to 400° C. The extrusion speed of the hot extrusion treatment is 5 mm / s, and the extrusion ratio is about 18;

[0070] Step 4: The Cu-25%Ta extruded rod obtained in step 3 is subjected to 4 passes of single rotary forging treatment to obtain a Cu-25%Ta single rotary forging wire; the diameter of the Cu-25%Ta extruded rod during the 4 passes of single rotary forging treatment changes as follows: φ7.0mm→φ6.6mm→φ6.2mm→φ5.9mm→φ5.6mm, and the corresponding processing amounts are 11.1%, 11.8%, 9.4%, and 9.9%, respectively;

[0071] Step 5: heat-treating the Cu-25%Ta single-spin forging wire obtained in step 4 at a temperature of 700° C. and a holding time of 3 h under argon atmosphere protection;

[0072] Step 6, subjecting the Cu-25%Ta primary rotary forging wire heat-treated in step 5 to 6 passes of secondary rotary forging treatment to obtain a Cu-25%Ta secondary rotary forging wire; during the 4 passes of secondary rotary forging treatment, the diameter of the primary Cu-25%Ta rotary forging wire changes as follows: φ5.6mm→φ5.3mm→φ5.0mm→φ4.7mm→φ4.4mm, and the corresponding processing amounts are 9.9%, 10.4%, 11.0%, 11.6%, and 12.3%, respectively;

[0073] Step seven, the Cu-25%Ta secondary swaging wire obtained in step six is ​​subjected to 6 drawing processes to obtain a Cu-25%Ta drawn wire, and the Cu-25%Ta composite wire is obtained after straightening and pickling; the diameter of the Cu-25%Ta secondary swaging wire during the 6 drawing processes changes as follows: φ4.4mm→φ4.22mm→φ4.05mm→φ3.88mm→φ3.72mm→φ3.58mm→φ3.44mm, and the corresponding processing amounts are 11.5%, 9.40%, 9.39%, 8.35%, and 8.18%, respectively.

[0074] After testing, the yield strength of the Cu-25% Ta composite wire prepared in this embodiment under tensile behavior is 473MPa, the tensile strength is 498MPa, the yield strength under compression behavior is 483MPa, and the conductivity is 68.1%IACS. Figure 1 and Figure 2As shown; after calculation, the total processing rate of the Cu-25%Ta composite wire prepared in this embodiment is 97.4%.

[0075] The above is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent change made to the above embodiment according to the technical essence of the invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A method for preparing a Cu-Ta composite wire, characterized in that: The method comprises the following steps: Step 1: Using a planetary ball mill to mix Cu powder and Ta powder to obtain Cu-Ta mixed powder; Step 2: Spark plasma sintering the Cu-Ta mixed powder obtained in step 1 to obtain a Cu-Ta columnar alloy; Step 3: hot extruding the Cu-Ta columnar alloy obtained in step 2 to obtain a Cu-Ta extruded rod; Step 4: performing a rotary forging process on the Cu-Ta extruded rod obtained in step 3 to obtain a Cu-Ta single rotary forging wire; Step 5, heat treating the Cu-Ta single rotary forging wire obtained in step 4; Step 6, subjecting the Cu-Ta primary rotary forging wire heat-treated in step 5 to secondary rotary forging to obtain a Cu-Ta secondary rotary forging wire; Step 7: The Cu-Ta secondary rotary forging wire obtained in step 6 is subjected to drawing treatment to obtain a Cu-Ta drawn wire, and the Cu-Ta composite wire is obtained after straightening and pickling.

2. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: The particle sizes of the Cu powder and Ta powder in step 1 are 5 μm to 15 μm and 65 μm to 50 μm, respectively.

3. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: The mass purity of the Cu powder and Ta powder in step 1 is above 99.95%.

4. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: The ball milling mixing treatment in step 1 adopts a rotation speed of 350 rpm, a time of 40 hours, a ball-to-material mass ratio of 15:1, and the grinding balls include 8 mm diameter grinding balls, 5 mm diameter grinding balls, and 2 mm diameter grinding balls in a quantity ratio of 3:5:2, and the ball milling atmosphere is argon atmosphere.

5. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: The mass fraction of Ta element in the Cu-Ta mixed powder in step 1 is 10% to 25%.

6. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: The spark plasma sintering process in step 2 is: firstly heating to 600°C at a heating rate of 100°C / min, then heating to 950°C at a heating rate of 50°C / min, and maintaining the pressure at 50 MPa for 10 minutes.

7. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: The density of the Cu-Ta columnar alloy in step 2 is 97% to 99%.

8. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: Before the hot extrusion treatment in step 3, the Cu-Ta columnar alloy is heat treated at 900° C. and kept warm for 30 minutes, and the mold for the hot extrusion treatment is preheated to 400° C. The extrusion speed of the hot extrusion treatment is 5 mm / s.

9. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: The heat treatment temperature in step 5 is 700° C. and the holding time is 3 h.

10. The method for preparing a Cu-Ta composite wire according to claim 1, characterized in that: The diameter of the Cu-Ta columnar alloy in step 2 is 30mm and the height is 25mm-27mm; the diameter of the Cu-Ta extruded rod in step 3 is 7mm; the diameter of the Cu-Ta extruded rod in the first rotary forging process in step 4 changes as follows: φ7.0mm→φ6.6mm→φ6.2mm→φ5.9mm→φ5.6mm, and the corresponding processing amounts are 11.1%, 11.8%, 9.4%, and 9.9%, respectively; the diameter of the Cu-Ta rotary forging wire in the second rotary forging process in step 6 changes as follows: φ5.6 mm→φ5.3mm→φ5.0mm→φ4.7mm→φ4.4mm, and the corresponding processing amounts are 9.9%, 10.4%, 11.0%, 11.6%, and 12.3%, respectively; the diameter change of the Cu-Ta secondary swaging wire during the drawing process described in step seven is: φ4.4mm→φ4.22mm→φ4.05mm→φ3.88mm→φ3.72mm→φ3.58mm→φ3.44mm, and the corresponding processing amounts are 11.5%, 9.40%, 9.39%, 8.35%, and 8.18%, respectively.

Citation Information

Patent Citations

  • Preparation method of copper-tantalum composite wire with high strength and high conductivity

    CN108213108A

  • Multi-layer multi-component composite shaped charge liner and preparation method thereof

    CN116858035A

  • Nanometer metal particle dispersion strengthening copper alloy and preparation method

    CN117947305A

  • Processes and / or Machines for Producing Continuous Plastic Deformation, and / or Compositions and / or Manufactures Produced Thereby

    US20220281005A1